2021
DOI: 10.1097/md.0000000000024796
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid operation for infectious thoracic and abdominal aortic aneurysms complicated with Bacillus Calmette–Guérin therapy for bladder cancer

Abstract: Rational: Bacillus Calmette–Guérin (BCG) intravesical instillation therapy is a widely used treatment for bladder cancer; however, an infectious aneurysm has been reported as a rare complication. Patient concerns: A 76-year-old man who underwent BCG intravesical instillation therapy for bladder cancer presented with prolonged dull back pain for 3 months. Diagnosis: Computed tomography (CT) revealed both thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Since 1988, 51 cases of a mycotic AAA attributable to BCG therapy have been reported. 4 , 5 , 8 , 10 , 11 , 12 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 In our patient, infectious aortitis had progressed rapidly, and a saccular AAA or pseudoaneurysm had developed within 2 months after BCG therapy. In hindsight, a follow-up CT scan should have been performed sooner to monitor for any aneurysmal changes.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Since 1988, 51 cases of a mycotic AAA attributable to BCG therapy have been reported. 4 , 5 , 8 , 10 , 11 , 12 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 In our patient, infectious aortitis had progressed rapidly, and a saccular AAA or pseudoaneurysm had developed within 2 months after BCG therapy. In hindsight, a follow-up CT scan should have been performed sooner to monitor for any aneurysmal changes.…”
Section: Discussionmentioning
confidence: 47%
“…To the best of our knowledge, to date, 20 patients (including our patient) with a mycotic aortoiliac aneurysm who had undergone EVAR after BCG therapy have been reported ( Table ). 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 All 20 patients were men, and their mean age at diagnosis was 71 years (range, 57-82 years). The aneurysms had been diagnosed at a mean interval of 19 months (range, 0-69 months) after BCG therapy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the 17 reports identified in our systematic review, and the additional case we report in this article, a total of 18 cases were identified [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Notable clinical characteristics extracted from these literature reports were patient’s age and gender, aneurysm location, extravascular involvement, time between most recent BCG instillation and admission, number of instillations, culture site, culture results, surgical treatment, discharge therapy, and reported outcomes ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Insgesamt erfolgte somit eine Volltextanalyse von 99 Manuskripten. Davon erfüllten 55 Publikationen [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,…”
Section: Ergebnisseunclassified